From Boardroom To Parliament - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
The benefits of state-owned enterprises are well known: cheap loans, favourable policies and little competition. Because of the perks they enjoy, these companies have often been criticised for not being hungry enough to maximise firm value, especially when their CEOs are not as well paid as those in the private sector. There is proof now that competition in the political job market helps mitigate the weak monetary incentives for CEOs in China. Interestingly, this means that state control and political connections may not be inconsistent with economic pursuits.